2013
DOI: 10.4236/ojee.2013.21004
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficiency Economics as a Resource for Energy Planning

Abstract: The objective of this work is a multi-criteria decision-making assessment that aims to facilitate the Energy-Efficiency Economics, introducing the Analytic Hierarchy Process (AHP) as part of power-system planning tool for an energyefficiency application. It addresses to include qualitative aspects in the decision-making agendas of energy-efficiency projects. The manuscript details the limitations of non-rigorous financial analysis and proposes an alternative for including energy-efficiency measures in discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We have developed different methods for determining the reliability of the potential of foreign companies [17][18][19][20]. The analysis showed that at the present time, a single and internationally recognized procedure does not exist.…”
Section: Research Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…We have developed different methods for determining the reliability of the potential of foreign companies [17][18][19][20]. The analysis showed that at the present time, a single and internationally recognized procedure does not exist.…”
Section: Research Relevancementioning
confidence: 99%
“…This is particularly important in the cases where special tax incentives or subsidies have been established [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%